2023
DOI: 10.1093/ejendo/lvad027
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after pediatric craniopharyngioma: the role of age at diagnosis and hypothalamic damage

Abstract: Objective Craniopharyngiomas (CP) are rare malformational tumors. Clinical presentation and outcome of pediatric patients with CP with specific regard to age at diagnosis is not clear. The aim of this cohort study was to determine clinical presentation and outcome in these patients diagnosed at different ages at diagnosis. Design Seven hundred and nine patients diagnosed with CP were recruited 1999-2021 in HIT-Endo, KRANIOPHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We reported that not only for the subgroup of patients younger than 6 years of age at CP diagnosis but also in the older age groups (at CP diagnosis), younger age was a risk factor for events in terms of progression and relapses. On the other hand, overall survival rates were similar in all age subgroups, indicating that radio-oncological treatment and/or surgical reinterventions were efficient rescue treatment modalities in case of relapse or progression of CP ( 22 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We reported that not only for the subgroup of patients younger than 6 years of age at CP diagnosis but also in the older age groups (at CP diagnosis), younger age was a risk factor for events in terms of progression and relapses. On the other hand, overall survival rates were similar in all age subgroups, indicating that radio-oncological treatment and/or surgical reinterventions were efficient rescue treatment modalities in case of relapse or progression of CP ( 22 ).…”
Section: Discussionmentioning
confidence: 95%
“…We have previously reported on the negative effect of young age at diagnosis on prognoses and outcome after CP ( 21 , 22 ). CPs are rarely diagnosed in the perinatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Morbid obesity is a frequent sequela in patients with childhood-onset craniopharyngioma [ 12 ]. Patients with anterior and posterior HI and HL are at the highest risk of developing obesity [ 94 ]. Morbid obesity can result in MetS, a well-known risk factor for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…The Kraniopharygeom 2007 project can be mentioned as a summary of this period. Such a German project, indeed, had/has the goal to study AC from 2007 in all its main features to provide information and increase the knowledge on the outcome [ 111 ] and about very specific aspects, like cerebral infarction [ 112 ] or cardiac remodeling in AC [ 113 ] or pregnancy after childhood onset AC [ 114 ].…”
Section: Introductionmentioning
confidence: 99%